Faktor penilaian personal dalam memenuhi kebutuhan akomodasi yang layak bagi penyandang disabilitas berdasarkan perspektif PP nomor 39 tahun 2020 tentang akomodasi yang layak untuk penyandang disabilitas dalam proses peradilan - Jonna Aman Damanik; Gunawan Widjaja (Literal: Disability Studies Journal, 2026)
As a state based on the rule of law, Indonesia has an obligation to ensure order and justice for all members of society without exception, including persons with disabilities. However, in practice persons with disabilities face a gap in accessing and getting reasonable accommodation in the judicial process, even though Indonesia ratified the UN Convention on the Rights of Persons with Disabilities through Law Number 19 of 2011, which was further implemented through Law Number 8 of 2016 concerning Persons with Disabilities. This study’s purpose is to demonstrate that personnel knowledge and education are key factors in providing good access and reasonable accommodation for persons with disabilities. The normative juridical method is the method chosen to be used in this research with an approach in the form of a statutory regulatory approach and a conceptual approach. The results indicate that although Law No. 8 of 2016, Government Regulation No. 39 of 2020, and Supreme Court Regulation (PERMA) No. 2 of 2025, and Guidelines Number 2 of 2023 concerning Reasonable Accommodation and Accessible and Inclusive Case Handling for Persons with Disabilities within the Judicial Process (2023) by the Attorney General’s Office have established a strong legal foundation for disability rights, the fulfillment of inclusive justice depends heavily on the implementation of personal assessments at every stage of the legal process. A personal assessment is a crucial instrument for minimizing interaction barriers and ensuring meaningful participation. For law enforcement officials, this instrument serves as a reference in determining the weight of evidence and legal accountability in a fair manner. This research concludes that strengthening technical regulations and improving officials' understanding of reasonable accommodation are the primary keys to achieving an accessible justice system for persons with disabilities.